Antifugal Activity Of Lactic Acid Bacteria Isolated From Malaysian Fermented Foods And Fruits - Belal J. Muhialdin
A total of 137 lactic acid bacteria isolated from fermented foods and fruits were evaluated for antifungal activity using dual agar overlay method against Aspergillus niger and A. oryzae. Twenty three isolates showed antifungal activity after 72 h incubation at 30°C. Three isolates were selected base on the highest antifungal activity and were identified using API 50CH and 16S rDNA as Lactobacillus pentosus G004 isolated from fermented guava juice, Lactobacillus fermentum Te007 and Pediococcus pentosaceus Te010 isolated from tempeh. All the isolates inhibited the growth of the mycelia and conidia germination of the fungi. The antifungal activity of the supernatants was evaluated using micro-titer plate assay. Antifungal activity of supernatant Lactobacillus fermentum Te007 and Pediococcus pentosaceus Te010 were diminished when treated with Proteinase K, RNase II and DNase indicating the presence of protein-like compounds. Antifungal activity of supernatant L. pentosus G004 was not destroyed when treated with the enzymes. L. fermentum Te007 and L. pentosus G004 produced heat stable compounds when heated at 90 and 121 °C. Supernatants of L. pentosus G004 were active at pH 3, 5, 6 and 7 while P. pentosaceus Te010 active at pH 5 and L. fermentum Te007 active at pH 3 and 7. The mixture of L. pentosus G004 and L. fermentum Te007 supernatants have high antifungal activity. LAB cells or their supernatants inhibited conidia germination when tested in selected foods. The growth of fungi was delayed for 23-40 days at 4 °C and 5-6 days at 20 and 30 °C in tomato puree, for 19-29 days at 4 °C and 6-12 days at 20 and 30 °C in processed cheese and 27-30 days at 4 °C and 12-24 days at 20 and 30 °C in commercial bread slices. The shelf life of bread slices prepared with added LAB cells or their supernatants to bread dough were extended seven days without chemical preservatives. This study demonstrates that the cells or supernatants of L. fermentum Te007, P. pentosaceus Te010 and L. pentosus G004 could be used as biopreservative in bakery products and other processed foods.